GENDER SENSITIZATION THROUGH LITERATURE – NEW APPROACHES - Sreevarsha. G. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender sensitization has emerged as a critical societal need, especially in contexts marked by gender inequity and discrimination. Literature, as a potent tool of reflection and resistance, plays a significant role in fostering gender awareness. This study explores how literary works, both historical and contemporary, contribute to gender sensitization by breaking gender stereotypes, questioning patriarchal norms, and promoting equality. By examining various genres, such as fiction, poetry, and essays from diverse cultural backgrounds, the study emphasizes the capacity of literature to challenge societal norms and create new approaches to gender equality. Through this exploration, the research aims to highlight the power of narrative in influencing attitudes and promoting social change, paving the way for deeper gender awareness and equality.